2020
DOI: 10.1073/pnas.2007248117
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale observations of electrical and mechanical manipulation of topological polar flux closure

Abstract: The ability to controllably manipulate complex topological polar configurations such as polar flux-closures via external stimuli may allow the construction of new electromechanical and nanoelectronic devices. Here, using atomically resolved in situ scanning transmission electron microscopy, we find that the polar flux-closures in PbTiO3/SrTiO3 superlattice films are mobile and can be reversibly switched to ordinary single ferroelectric c or a domains under an applied electric field or stress. Specifically, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 44 publications
(102 reference statements)
0
35
0
1
Order By: Relevance
“…Aberration corrected scanning transmission electron microscopy (STEM) allows the multiferroic research community to investigate domain wall (DW) topologies at the sub-atomic scale. [24][25][26][27][28][29][30][31] Using STEM we can quantify the atomic displacements and thus polarisation changes at and within topologies. Recently, Campanini, M., et al 32 Additionally, we have found that polar vortex topologies were present in regions where out-ofphase boundaries (OPB) defects are spaced between 5 to 8 perovskite cells apart.…”
Section: Introductionmentioning
confidence: 99%
“…Aberration corrected scanning transmission electron microscopy (STEM) allows the multiferroic research community to investigate domain wall (DW) topologies at the sub-atomic scale. [24][25][26][27][28][29][30][31] Using STEM we can quantify the atomic displacements and thus polarisation changes at and within topologies. Recently, Campanini, M., et al 32 Additionally, we have found that polar vortex topologies were present in regions where out-ofphase boundaries (OPB) defects are spaced between 5 to 8 perovskite cells apart.…”
Section: Introductionmentioning
confidence: 99%
“…[ 49 , 62 , 63 , 64 , 65 , 66 , 67 ] In addition, the interaction of lattice, orbitals, charges, and spins at the heterogeneous interface produces peculiar physical properties, such as “improper ferroelectricity” in short‐period superlattices, ordered vortex arrays in mid‐period superlattices, and flux‐closed domain structures in large‐period superlattices. [ 68 , 69 , 70 , 71 , 72 , 73 ] These phenomena are important for researchers to understand the involved physical phenomena. The influence of this novel properties on the energy storage characteristics of multilayer dielectric needs to be explored.…”
Section: Basic Theory Of Multilayer Structure Dielectricsmentioning
confidence: 99%
“…As the polarization can be coupled with other intrinsic properties as well as external stimuli, the ferroelectric exhibits various physical properties, and is considered as a critical component in modern and future electronic elements. [ 14 , 15 , 16 , 17 , 18 , 19 ] As shown in Figure 1b , under the external stimuli of electric, stress, light, and magnetic fields, the ferroelectric enjoys multiple coupling effects of piezoelectric, [ 20 ] electric‐optic, [ 21 , 22 , 23 ] magneto‐electric, [ 24 , 25 ] piezo‐magnetic, [ 26 ] and magneto‐optic [ 27 ] effects, among others. [ 28 , 29 , 30 ] Based on these unusual physical properties, the ferroelectric materials have been employed for widespread applications such as pyroelectric sensors, piezoelectric actuators, electro‐optic modulators, and nonvolatile memories, [ 28 , 29 , 30 ] and other novel applications following the exploration of unusual polarization domain structures have also been conceived.…”
Section: Introductionmentioning
confidence: 99%